STRATEGI PENGELOLAAN SUMBER DAYA AIR DI DAERAH ALIRAN SUNGAI AYUNG SECARA TERINTEGRASI - Kerta Arsana, I Gusti Ngurah (Jurnal Ilmiah Teknik Sipil, 2012)
Water resources potency of Ayung river should be developed more optimal. Ayung river flow across four regencies, that are: Bangli, Gianyar, Badung, and Denpasar. In line with growth sum up the resident and increasing of society result the change of environment function which is negative impact to the water resource continuity. The mentioned claim the development and integrated river basin water resource management. Formulation analysis of water resource management strategy at area watershed of Ayung river uses the SWOT analysis. This formulation compilation to determine the especial action pattern to realize of water resource management integrated. Result of SWOT analysis indicate that the step plan of water resource management integrated can be started from reinforcement of management institute, more technical policy preparation in area level, forming place the coordination, and make-up of human resource. This strategy requires to be allowed for implementation intactly and in phases.
Keywords: management strategy, integration, formulation analysis